Teorias democráticas diante da nova gramática de organização da sociedade e da relação entre o Estado e a sociedade - Toledo, Rodrigo Alberto [UNESP] (My University, 2013)
This article is about the democratic theoretical conceptions reformulated in face of the new social rules in which actors showed up claiming repressed social repressed from the second half of the XX century. In this article an approach of the main contributions of the dimensions of the conception of democracy. As a result, we present that the institutional innovations that came from a process of institutionalism of democracy have built a participative and inclusive ideal of social groups that so far were apart from the decision process in politics.

O presente artigo aborda as concepções teóricas democráticas reformuladas diante da nova gramática social em que atores emergiram clamando por demandas sociais reprimidas a partir da segunda metade do século XX. Desenvolveu-se, neste trabalho, uma abordagem sobre as principais contribuições das dimensões da concepção democrática. Como resultado, apresentamos que as inovações institucionais, advindas do processo de uma institucionalidade da democracia, constituíram um ideal participativo e inclusivo de grupos sociais, até então, apartados do processo político-decisório.
Democratic theories facing the new rules of society organization and the relationship between the State and the Society
Keywords: Democracy; Participation; State and Government; Democratic theories; Decision making process; Democracia; Participação; Estado e Governo; Teorias democráticas; Processo decisório